The Aim of Religious Moderation is to Overcome Identity Conflicts - Anwar, Saiful; Alwalid, Mohammed Alghiffar; Nizar, Nizar (International Journal of Law and Society, 2024)
This research explains religious moderation in overcoming identity conflicts and creating religious harmony. Identity conflicts occur very often, both on a national and international scale. This research was conducted using a qualitative approach. This type of research is library research. Data analysis uses data reduction, presentation, and conclusion drawing/verification steps. This research found several ways to overcome identity conflicts and create religious harmony, respecting the worship rituals of other religions, implementing noble morals between religious communities, and building cooperation between religious communities. Conflict occurs not only in differences or misunderstandings within a group, but more in identity conflict at the cognitive and emotional level of the individual. Conflict reflects the gap between the values, beliefs, norms, and demands inherent in individual and group identities. So then moderate Islam with the concept of wasathiyah became the dividing line and resolved identity conflicts.